Trait-based community assembly and functional strategies across three subtropical karst forests, Southwestern China - Jiang, Yong; Chen, Zhenqing; Lin, Haili; Deng, Rongxin; Liang, Zhihui; Li, Yuling; Liang, Shichu (Frontiers in Plant Science, 2024)
Variations in community-level plant functional traits are widely used to uncover adaptation strategies of vegetation under various environmental gradients. Moreover, studying functional variation across different forest types aids in understanding the mechanisms through which environment and functional strategies shift drive community structure. Based on five plant functional traits including four leaf and one wood traits for 150 woody species, we analyzed shifts in the community-weighted mean trait values in three forest types in a karst forest landscape: deciduous, mixed and evergreen forests. We also assessed the relative contributions of stochastic processes, environmental filtering, and niche differentiation to drive community structure using a trait-based null model approach. We found marked changes in functional strategy, from resource acquisition on dry, fertile soil plots in deciduous forests to resource conservation on moist, infertile soil conditions in evergreen forests. The trait-based null model showed strong evidence of environmental filtering and convergent patterns in traits across three forest types, as well as low niche differentiation in most functional traits. Some evidence of overdispersion of LDMC and LT occurred to partially support the recent theory of Scheffer & Van Nes that competition could result in a clumped pattern of species along a niche axis. Our findings suggest a change on environmental gradient from deciduous to evergreen forest together with a shift from acquisitive to conservative traits. Environmental filtering, stochastic processes, niche differentiation and overdispersion mechanisms together drive community assembly in karst forest landscapes. These findings will contribute to a deeper understanding of the changes in functional traits in karst plants and their adaptative strategies, and have important implications for understanding other community assemblies at subtropical forest system.